2012
DOI: 10.1111/j.1365-3024.2012.01379.x
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in anti‐Leishmania IgG3 and IgG1 after cutaneous leishmaniasis lesion healing is correlated with the time of clinical cure

Abstract: For better efficiency in the establishment of American tegumentary leishmaniasis clinical cure, the World Health Organization suggests that the clinical criteria are supported by serologic data. The present study aims to investigate the dynamics of IgG subclass production in clinical evolution post-treatment of cutaneous leishmaniasis (CL). Paired sera from 23 subjects with CL resulting from Leishmania braziliensis infection were studied during the active lesion phase (aCL) and after clinical cure post-therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
4
17
0
1
Order By: Relevance
“…Interestingly, the IgG3 levels decreased among NR patients after VL treatment and remained decreased until the end of follow-up, very similar to what was observed for the CD4 + and CD8 + T lymphocyte activation levels. This result corroborates what has been described in the tegumentary form of leishmaniasis [39], suggesting IgG3 as a possible clinical remission marker for VL that deserves more attention.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, the IgG3 levels decreased among NR patients after VL treatment and remained decreased until the end of follow-up, very similar to what was observed for the CD4 + and CD8 + T lymphocyte activation levels. This result corroborates what has been described in the tegumentary form of leishmaniasis [39], suggesting IgG3 as a possible clinical remission marker for VL that deserves more attention.…”
Section: Discussionsupporting
confidence: 91%
“…An ELISA was performed as previously described by Fagundes-Silva et al (2012), with certain modification [39]. Briefly, the only difference was the antigen, since L .…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, the diagnosis of TL is based on clinical criteria associated with the laboratory diagnosis (8); however, problems related to the sensitivity of the tests have been described, since a significant percentage of patients are classified as false negative in the serological assays employing antigenic Leishmania preparations, due to the low levels of antileishmanial antibodies encountered in their serum samples (23). In relation to specificity, an important problem for the TL serodiagnosis resides in the crossreactivity of the antigens with sera from noninfected subjects living in areas of disease endemicity, as well as with serum samples from patients developing related pathologies, such as Chagas disease, which can present cross-reactivity in the serological analysis performed (42).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the serum concentration of antileishmanial antibodies can be directly related to the parasite load and to the time of exposure to Leishmania antigens (21)(22)(23). Although the role of antibodies in TL is not completely understood, evidence has shown that the humoral response determined by specific IgG reactivity to Leishmania antigens could well be used as an indicator of the development of the disease, since some authors have positively correlated the clinical cure of disease with a decrease in the antileishmanial antibody titers, as well as to assist the clinical follow-up during and after healing by the treatment of the patients (23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…Anam et al (144) also hinted at a possible (diagnostic) role for L. donovani-specific IgG3 antibody isotype detection. While the IgG3 antibody level decreases significantly posttreatment (148,149), the pharmacodynamic value of this marker is probably very low, as the time to normalcy for IgGs is longer than 3 months for both CL and VL patients (150)(151)(152)(153)(154).…”
Section: Identified Biomarkersmentioning
confidence: 99%